Long-term oncological prognosis after curative-intent liver resection for hepatocellular carcinoma in the young versus the elderly: multicentre propensity score-matching study. Issue 1 (27th January 2022) - Pu, Jia-Le; Chen, Zhong; Yao, Lan-Qing; Feng, Ji-Ye; Diao, Yong-Kang; Guan, Ming-Cheng; Li, Ju-Dong; Chen, Zheng-Liang; Zhou, Ya-Hao; Wang, Hong; Gu, Wei-Min; Li, Jie; et al.
Abstract: Background: Hepatocellular carcinoma (HCC) is the most common malignancy in the elderly worldwide, but it is also common among younger individuals in areas with endemic hepatitis B virus infection. The differences in long-term oncological prognosis of young versus elderly patients after R0 liver resection for HCC were explored in this study. Methods: Using a Chinese multicentre database, consecutive patients who underwent R0 liver resection for HCC between 2007 and 2019 were analysed retrospectively. After excluding middle-aged (36–69 years old) patients, overall survival (OS), cancer-specific survival (CSS), and recurrence were compared between young (35 years or younger) and elderly (70 years or older) patients using propensity score matching (PSM). Results: Among 531 enrolled patients, there were 192 (36.2 per cent) and 339 (63.8 per cent) patients categorized as young and elderly respectively. PSM created 140 pairs of matched patients. In the PSM cohort, 5-year OS was comparable for young versus elderly patients (51.7 versus 52.3 per cent, P  = 0.533). Young patients, however, had a higher 5-year cumulative recurrence rate (62.1 versus 51.6 per cent, P  = 0.011) and a worse 5-year CSS rate (54.0 versus 64.3 per cent, P  = 0.034) than elderly patients. On multivariable Cox regression analyses, young patient age remained independently associated with an increased recurrence rate (hazard ratio 1.62, P  = 0.016) and a decreased CSS rate (hazard ratio 1.69, P  = 0.021) compared with older age. Conclusion: Following R0 liver resection for HCC, younger patients were at a higher risk of recurrence, and elderly patients had a better CSS rate. Thus, enhanced surveillance for HCC recurrence should be implemented for young patients. Abstract : Using a large multicentre database from China, the clinicopathological features and long-term oncological prognosis after R0 liver resection for hepatocellular carcinoma between the young (35 years and less) and elderly (at least 70 years old) were characterized and compared. Based on propensity score matching and multivariable Cox regression analyses, this study showed that young patients had a higher recurrence rate and a worse cancer-specific survival rate than elderly patients.